Perspectivas sobre a teoria da objetividade de F. H. Jacobi na Querela do Espinosismo - Chermont, Arthur Valença Macedo (2024)
This text will proceed as follows. In its first part (2.) we will focus on the Spinoza quarrel and the link between Jacobi and Spinoza. We will begin historically, with the first two sections (2.1 and 2.2) contextualizing the quarrel and Lessing's confession of Spinoza to Jacobi, highlighting the appropriate intertextualities. We will continue with a brief methodological perspective, in order to bring further precision to the author's own terms, and then begin the last section of this first part (2.3), in which we will address the peculiarity of Jacobi's reading and opposition to Spinoza (or what the author understands by Spinoza). Our second part focuses on the author's theory of objectivity with two sections (3.1 and 3.2). The first focuses on his epistemological foundation, nominally the concept of belief; the second studies the core of his theory of objectivity: the program of his realism in overcoming the modern conception of consciousness. The purpose of the text, therefore, is to understand Jacobi's theory of objectivity as a party in the Spinoza dispute, which defined the intellectual horizon of the time and whose historical consideration is our initial starting point